2016
DOI: 10.1038/ncomms13229
|View full text |Cite
|
Sign up to set email alerts
|

Self-motion evokes precise spike timing in the primate vestibular system

Abstract: The accurate representation of self-motion requires the efficient processing of sensory input by the vestibular system. Conventional wisdom is that vestibular information is exclusively transmitted through changes in firing rate, yet under this assumption vestibular neurons display relatively poor detection and information transmission. Here, we carry out an analysis of the system's coding capabilities by recording neuronal responses to repeated presentations of naturalistic stimuli. We find that afferents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 68 publications
5
52
0
Order By: Relevance
“…; Jamali et al . ). Indeed, the gain–decrease paradigm did not result in persistent changes in SS activity, but only in changes in CS activity that may influence plasticity in the vestibular and cerebellar nuclei (Pugh & Raman, ; De Zeeuw et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Jamali et al . ). Indeed, the gain–decrease paradigm did not result in persistent changes in SS activity, but only in changes in CS activity that may influence plasticity in the vestibular and cerebellar nuclei (Pugh & Raman, ; De Zeeuw et al .…”
Section: Discussionmentioning
confidence: 97%
“…Besides firing rates, the temporal pattern of spike timings also carries important information about brain functions. For instance, it has been shown that temporal patterns encode the information of auditory (Machens et al, 2001;Narayan et al, 2006;Wang et al, 2007;Fukushima et al, 2015;Krause et al, 2017), gustatory (Di Lorenzo and Victor, 2003), motor (Vargas-Irwin et al, 2015), olfactory (MacLeod et al, 1998), somatosensory (Harvey et al, 2013), vestibular (Jamali et al, 2016), and visual (Mechler et al, 1998;Victor and Purpura, 1998;Reich et al, 2001;Carrillo-Reid et al, 2015) systems, as well as behavioral adaptation (Logiaco et al, 2015) and sleep (Tabuchi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, by removing rate dependence from the SPIKEdistance, Satuvuori et al (2017) proposed the RI-SPIKE-distance as a distance purely sensitive to timing. The spike train distances developed so far have been used in a number of studies for the analysis of neural firing patterns (MacLeod et al, 1998;Mechler et al, 1998;Victor and Purpura, 1998;Machens et al, 2001;Reich et al, 2001; Di Lorenzo and Victor, 2003;Narayan et al, 2006;Wang et al, 2007;Harvey et al, 2013;Fukushima et al, 2015;Logiaco et al, 2015;Vargas-Irwin et al, 2015;Jamali et al, 2016;Krause et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although these findings do not distinguish adequate stimuli for activation of these networks, they do indicate that independent processing streams to the periaqueductal gray, locus coeruleus, and serotonergic/non‐serotonergic raphe cells are affected by galvanic stimulation. Since these sites are also modulated during nociception, they are potential mediators of interactions between vestibular stimulation and pain perception that could alter normal coding via precise spike timing . One predicts similar results for caloric stimulation in the ear canal.…”
Section: Discussion/observationsmentioning
confidence: 81%